High- and low-affinity binding of GRO alpha and neutrophil-activating peptide 2 to interleukin 8 receptors on human neutrophils. - Schumacher, C (1992)
GRO alpha and neutrophil-activating peptide 2 (NAP-2), like their analog interleukin 8 (IL-8), are considered to be inflammatory mediators since they recruit and activate neutrophil leukocytes. After introduction of tyrosines by substitution for other residues at the C terminus, GRO alpha and NAP-2 were labeled with 125I and used for binding studies. A total of 60,000-90,000 receptors per neutrophil were found for either ligand. Of these 30-45% were of high affinity with a mean Kd value of 0.3 and 0.7 nM for GRO alpha and NAP-2, respectively, and 55-70% of low affinity (Kd = 30 nM). Two proteins of approximately 70 kDa and 44 kDa (p70 and p44) were specifically cross-linked with labeled GRO alpha, NAP-2, and IL-8. Unlabeled IL-8 fully inhibited this cross-linking and the binding of labeled GRO alpha or NAP-2 to the high-affinity sites on neutrophils or neutrophil membranes. Treatment of membranes with digitonin resulted in the preferential solubilization of a single receptor species, corresponding to p44, that bound GRO alpha and NAP-2 with low affinity (Kd = 30 nM) and IL-8 with high affinity (Kd = 0.4 nM). Exposure of neutrophil membranes to 100 microM guanosine 5'-[gamma-thio]triphosphate led to a 75-fold increase of the Kd in approximately 60% of the IL-8 receptors. High-affinity receptors for GRO alpha and NAP-2 were similarly affected. In contrast, guanosine 5'-[gamma-thio]triphosphate had no effect on the binding of IL-8 to p44 solubilized by digitonin. These results demonstrate that human neutrophils bear two classes of receptors for GRO alpha, NAP-2, and IL-8 (p70 and p44) that may differ in their mode of interaction with GTP regulatory proteins.